KEMAMPUAN CALON GURU SEKOLAH DASAR DALAM MENGATASI KESULITAN BELAJAR SISWA - Sudarwo, Raden; Adiansha, Adi Apriadi (Jurnal Ilmiah Mandala Education (JIME), 2021)
The problem of learning difficulties in students does not look at the intellectual abilities of students. Many students with low intelligence can achieve high learning achievement, exceeding the intelligence of students with high intelligence, but it also cannot be denied that high intelligence provides great opportunities for students to achieve high learning achievement. The purpose of this study was to determine the ability of prospective elementary school teachers in overcoming learning difficulties in students. The type of research used is descriptive qualitative research. The approach used in this study is qualitative. The instruments used in this study were observation, interviews, and documentation. The data analysis technique is descriptive qualitative data analysis technique. The results of this study indicate that there are several efforts made by prospective teachers in overcoming learning difficulties experienced by students including difficulties in learning to read, difficulties in learning to write, and difficulties in learning to count. The teacher's way of dealing with students who have learning difficulties. 1) Selecting and determining learning strategies that will be used by teachers to overcome learning difficulties experienced by students. 2) Selecting and establishing a learning approach that is by the conditions experienced by students, 3) Selecting and determining learning methods and techniques that are considered the most appropriate and effective so that they can be used as teacher guidelines in carrying out their teaching activities, 4) Designing and preparing teaching aids that appropriate and interesting for students to help students in the learning process. Many things are done by teachers to overcome learning difficulties. Teachers need to provide opportunities for students to ask things that have not been understood about the lessons described, provide guidance to students who have learning difficulties, be it group guidance or individual guidance.